The virtuous therapist : ethical practice of counseling & psychotherapy - Cohen, Elliot D.; Cohen, Gale Spieler; Gale, Spider Cohen (Belmont, CA : Brooks/Cole Wadworth, 1999)
In The Virtuous Therapist, authors Elliot D. Cohen and Gale Spieler Cohen provide a systematic, philosophical approach to mental health ethics. Their comprehensive model of ethical decision making is developed to a number of difficult ethical problems counselors will experience. The issues raised in the book are timely, ethically engaging, and of practical importance to those working in the field.
Includes bibliographical references (p. 259-267) and index.
Keywords: Counselors -- Professional ethics; Psychotherapists -- Professional ethics; Counseling -- Moral and ethical aspects; Psychotherapy -- Moral and ethical aspects